Celeridad y auditorías, una conexión necesaria para la eficiencia fiscal en las entidades públicas del departamento del choco - Quinto Mosquera, Yelison; Moreno Ibarguen, Saidy Yorleny (Universidad Antonio Nariño, 2023)
The principle of celerity is a guiding principle in everything that has to do with the administrative branch, so its observance must be respected in all its areas and given in a timely manner in each case, otherwise, it is likely that an administrative proceeding against whoever fails at the beginning, whether it is a judicial operator acting in the administrative jurisdiction or an official of the branch itself. Audits, on the other hand, are generally processes that seek to verify the guidelines and guarantee the concurrence of the requirements and formalities that the law requires in the performance of the activities of a given institution. On the other hand, when we talk about fiscal management we are focusing on the activity that focuses on monitoring the management of money belonging to the nation